Pengaruh Modul Argument Driven Inqiry terhadap Kesadaran Lingkungan Mahasiswa - Eka Imbia Agus Diartika (CV Putra Publisher, 2024)
This research aims to test biology students' environmental awareness using three different learning materials, one of which is a module with argument-based inquiry. This module is applied in the learning process using quasi-experimental research with a non-randomized pretest-posttest control group design. This research was conducted in 3 classes of Biology Education undergraduate students, State University of Malang, who took the Basic Environmental Science course during April-May 2020. Learning was carried out online over 3 meetings, with learning activity 1 about the concept of waste, learning activity 2 about the impact of pollution waste, and learning activity 3 about solving environmental problems caused by waste. The experimental class was taught using the ADI module, the positive control class was taught using the ADI model, and the negative control class was taught using PowerPoint. Students' pretest-posttest environmental awareness scores were analyzed using Ancova. The results of the Ancova environmental awareness test for biology students show that the significance is 0.930, so there is no difference in environmental awareness between students who use the ADI module, ADI model, and PowerPoint.